Beyond Bureaucratic Limits and Social Challenges: Examining Hindrances to MSMEs as a Source of Indonesian Foreign Exchange - Parlina, Seli; Hudaya, Aldian (Institut Agama Islam Negeri (IAIN) Bone, 2025)
Micro, Small, and Medium-Sized Enterprises (MSMEs) are not just economic entities but also the pillars of Indonesian economy, representing the people's economic strength and holding tremendous potential as a source of foreign exchange for the country. However, this potential is often hindered by top-level structural factors such as complex bureaucracy, bias towards more affluent investors, and bottom-level challenges like the lack of digital literacy, limited market access, and constrained production capacities. This paper delves into these hindrances from scientific Management and Sociology perspectives using a qualitative approach through interviews and literature studies. It serves as a critical reflection on the urgent need for alignment between national policies and social realities, a crucial step towards achieving national economic independence through the empowerment of MSMEs.